1983
DOI: 10.4315/0362-028x-46.6.514
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Factors Affecting Growth and Production of Antimicrobial Substances by Streptococcus lactis subsp. diacetylactis S1-67/C

Abstract: The present study pertains to the effect of nutritional factors on the growth and production of antimicrobial substances (AS) by Streptococcus lactis subsp. diacetylactis S1-67/C. Among nine media tested, yeast extract dextrose broth supported good growth and maximum production of AS. Addition of beef extract and yeast extract at 1.0 and 0.6% levels, respectively, increased growth as well as production of AS. Of ten carbohydrates examined, maximum production of AS was achieved with 1% glucose followed by fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
4
3
0
Order By: Relevance
“…lactis subsp. diacetylactis was able to produce substantial amounts of antifungal substance in a narrow range of pH (5.5-7), although maximal production occurred at pH 6.8 (Batish et al, 1997;Reddy & Ranganathan, 1985). Similar data were obtained by Corsetti et al (1998), who reported an optimal production of inhibitory substances by Lactobacillus sanfranscico CB1 at pH 6.…”
Section: Effect Of Phsupporting
confidence: 85%
See 2 more Smart Citations
“…lactis subsp. diacetylactis was able to produce substantial amounts of antifungal substance in a narrow range of pH (5.5-7), although maximal production occurred at pH 6.8 (Batish et al, 1997;Reddy & Ranganathan, 1985). Similar data were obtained by Corsetti et al (1998), who reported an optimal production of inhibitory substances by Lactobacillus sanfranscico CB1 at pH 6.…”
Section: Effect Of Phsupporting
confidence: 85%
“…Reddy and Ranganathan (1985) have reported that the greatest production of antifungal metabolites by Lc. lactis subsp.…”
Section: Temperature and Incubation Periodmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies carried out by some investigators revealed that maximal production of antibiotic substances occurred after 96 hrs (Reddy &Ranganathan, 1985;Sujathaet al, 2005;Mustafa, 2009).This is in agreement with our results (Figure 8). In contrast, the highest biomass and antibiotic activity was observed at an incubation time of 72 hrs by some other investigators (Srinivasuluet al, 2002).…”
supporting
confidence: 83%
“…In contrast, it was showed that maximum antibiotics production was obtained at acidic pH (Reddy &Ranganathan, 1985;VenkataDasu and Panda, 1999;Jichenget al, 2008). It has been reported that maximum production of bacitracin and other antibiotics occurred at alkaline pH (Basilioet al, 2003).…”
mentioning
confidence: 99%